Aqueous zinc ion battery electrolyte and preparation method and application thereof
By adding O-phosphate ethanolamine to the electrolyte of the aqueous zinc ion battery, an interface protective layer is generated, which solves the problem of side reactions in the negative electrode of the battery, and significantly improves the stability and cycle life of the battery.
Patent Information
- Application Number
- CN202411889865.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
In practical applications, aqueous zinc ion batteries face side reactions of the negative electrode electrolyte interface, such as hydrogen evolution, corrosion and passivation, which leads to deterioration of battery performance and shortening of cycle life.
The electrolyte solution was added to the electrolyte, and through the chemical bond formation and electrochemical decomposition reaction with the zinc metal surface, an organic and inorganic hybrid interface protective layer was formed in situ, preventing water molecules from contacting the zinc negative electrode, and inhibiting side reactions and the growth of zinc dendrites.
It significantly improves the negative interface stability and cycle life of the aqueous zinc ion battery, and improves the overall performance and safety of the battery.
Smart Images

Figure CN119650891A_ABST
Abstract
Description
Technical Field
[0001] The invention provides an aqueous zinc ion battery electrolyte and a preparation method thereof, belonging to the technical field of electrolytes. Background Art
[0002] The continuous growth of global energy demand and the large-scale access of renewable energy have brought great challenges to the stability of power systems. Energy storage technology can effectively balance power supply and demand and enhance the reliability and stability of the power grid, and its position in the new power system is becoming increasingly important. As an emerging electrochemical energy storage technology, aqueous zinc-ion batteries have gradually become one of the main choices for large-scale energy storage in future power systems with their excellent safety and environmental friendliness. However, aqueous zinc-ion batteries face many challenges in practical applications, especially side reactions at the interface of the negative electrode electrolyte, such as hydrogen evolution, corrosion and passivation. The occurrence of hydrogen evolution reaction not only leads to the deterioration of the acid-base environment of the interface electrolyte, but also reduces the charge and discharge efficiency of the battery; the corrosion of the negative electrode material may cause the battery performance to deteriorate and increase the risk of short circuit; the passivation process will form an uneven insulating layer on the surface of the negative electrode, which limits ion conduction and slows down the reaction rate. In addition, the uneven deposition process of zinc ions will lead to the uncontrolled growth of dendrites at the negative electrode interface, which seriously affects the cycle life and overall reliability of the battery. Therefore, there is an urgent need to solve these technical problems by regulating the interface stability of the negative electrode electrolyte in terms of structure and composition, so as to improve the stability and cycle life of the battery.
[0003] Currently, researchers mainly use methods such as physical coating or chemical deposition to construct a non-in-situ solid electrolyte interface layer on the surface of the negative electrode of zinc-ion batteries. Although these technologies can effectively form the desired interface structure under laboratory conditions, their processes are relatively complicated, and it is difficult to accurately control the coating uniformity in actual operation. In addition, existing coating technologies are often difficult to adapt to the needs of large-scale production, resulting in its limitations in commercial applications. Therefore, this method of establishing an interfacial protective layer is not yet practical, and there is an urgent need to develop a simpler, controllable and industrially suitable strategy to solve the challenges faced by existing technologies and promote the further popularization and application of aqueous zinc-ion batteries.
[0004] The additive molecule is known for its unique phosphate group, which enables the lone pair of electrons of the phosphorus atom to form coordination bonds with the empty orbitals on the surface of zinc metal. This coordination is the basis for the interaction between O-phosphoethanolamine molecules and the surface of zinc metal, which in turn enables these molecules to exhibit good adsorption in an electrochemical environment. Specifically, O-phosphoethanolamine molecules can be rapidly and effectively chemically adsorbed to the surface of zinc metal through bonding. O-phosphoethanolamine molecules can not only preferentially adsorb to the surface of the zinc negative electrode, but also undergo electrochemical decomposition reactions to form an organic-inorganic hybrid interface protective layer, which prevents direct contact between water molecules and the zinc negative electrode, inhibits the occurrence of negative electrode interface side reactions and the growth of zinc dendrites, and enhances the stability of the negative electrode interface. This mechanism not only helps to improve the overall performance of zinc-ion batteries, but also provides strong support for extending their cycle life. Therefore, the application of additive molecules is of great significance in improving the safety and efficiency of zinc metal batteries. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an aqueous zinc ion battery electrolyte and a preparation method and application thereof. The present invention adds O-phosphoethanolamine to the electrolyte, and the O-phosphoethanolamine molecules not only form a strong chemical bond with zinc metal, but also may trigger an electrochemical decomposition reaction, further promoting the formation of an interface layer. The O-phosphoethanolamine molecules can not only preferentially adsorb to the surface of the zinc negative electrode, but also undergo an electrochemical decomposition reaction to form an organic-inorganic hybrid interface protective layer, prevent water molecules from directly contacting the zinc negative electrode, inhibit the occurrence of negative electrode interface side reactions and the growth of zinc dendrites, and enhance the stability of the negative electrode interface.
[0006] The present invention is achieved by adopting the following technical solutions:
[0007] An aqueous zinc ion battery electrolyte comprises zinc salt, O-phosphoethanolamine and water.
[0008] Preferably, the concentration of O-phosphoethanolamine in the electrolyte is 0.01 to 2 mol / L.
[0009] Further preferably, the concentration of O-phosphoethanolamine in the electrolyte is 0.1 to 1 mol / L.
[0010] Preferably, the zinc salt is any one or more of zinc sulfate, zinc chloride, zinc nitrate and zinc trifluoromethanesulfonate.
[0011] Further preferably, the concentration of zinc salt in the electrolyte is 0.1 to 3 mol / L.
[0012] More preferably, the concentration of zinc salt in the electrolyte is 1 to 2 mol / L.
[0013] The method for preparing the aqueous zinc ion battery electrolyte of the present invention comprises the following steps:
[0014] Zinc salt and O-phosphoethanolamine are added into water, and mechanical stirring and ultrasonic treatment are carried out successively at room temperature to obtain an aqueous zinc ion battery electrolyte.
[0015] Preferably, the mechanical stirring speed is 100 r / min to 600 r / min, and the mechanical stirring time is 5 min to 60 min.
[0016] Preferably, the ultrasonic power is 50W to 600W, and the ultrasonic time is 5min to 60min.
[0017] The aqueous zinc ion battery is prepared by using the aqueous zinc ion battery electrolyte of the present invention, and the aqueous zinc ion battery includes a half cell or a full cell.
[0018] Compared with the prior art, the present invention has the following beneficial technical effects:
[0019] The invention prepares an electrolyte for an aqueous zinc ion battery by adding an additive O-phosphoethanolamine to a zinc salt aqueous solution. The electrolyte can generate an interface protective layer in situ at the interface of the negative electrode electrolyte, and can effectively improve the stability and cycle life of the aqueous zinc ion battery. O-phosphoethanolamine contains a phosphate group, and the lone pair of electrons of the phosphorus atom can form a coordination bond with the empty orbital on the surface of the zinc metal. This characteristic enables O-phosphoethanol to be efficiently chemically adsorbed on the surface of the zinc metal in an electrochemical environment. When these molecules contact the zinc surface, they not only firmly adhere through strong bonding, but also may trigger a series of electrochemical decomposition reactions, thereby generating a protective interface in situ, effectively limiting the possibility of water molecules directly contacting the zinc negative electrode. By reducing the interaction between water molecules and zinc metal, this protective layer significantly reduces the probability of potential side reactions, thereby improving the stability between the negative electrode and the electrolyte. This mechanism is crucial to improving the performance and safety of zinc ion batteries, and also provides good support for extending the service life of the battery.
[0020] The electrolyte of the present invention undergoes electrochemical decomposition on the surface of the negative electrode to generate an organic-inorganic hybrid interface protective layer, regulates the zinc negative electrode / electrolyte interface characteristics, inhibits the occurrence of interface side reactions, and simultaneously inhibits the uncontrolled growth of interface zinc dendrites. Therefore, the electrolyte of the present invention can significantly enhance the stability and reversibility of the negative electrode, while improving the cycle stability and service life of the aqueous zinc ion battery. In addition, the electrolyte additive proposed by the present invention has low cost, high biocompatibility and a wide range of raw material sources, and these characteristics are conducive to promoting the promotion of aqueous zinc ion batteries in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The aqueous zinc ion symmetric battery prepared in Comparative Example 1 and Example 1 was -2 , the deposition capacity is 1 mAh cm -2 The time voltage curve below;
[0022] Figure 2 The aqueous zinc ion symmetric battery prepared in Comparative Example 1 and Example 4 was -2 , the deposition capacity is 5 mAh cm -2 The time voltage curve below;
[0023] Figure 3 The rate performance curves of the aqueous zinc ion symmetric batteries prepared in Comparative Example 1 and Example 5 at different current densities;
[0024] Figure 4 The aqueous zinc ion Zn / / Cu battery prepared in Comparative Example 1 and Example 3 was tested at a current density of 1 mA cm -2 , the deposition capacity is 0.5 mAh cm -2 Coulomb efficiency curve below;
[0025] Figure 5 The aqueous zinc ion Zn / / Cu battery prepared in Comparative Example 1 and Example 2 was tested at a current density of 5 mA cm -2 , the deposition capacity is 1 mAh cm -2 Coulomb efficiency curve below;
[0026] Figure 6 The negative electrode X-ray diffraction curves of the aqueous zinc ion symmetric batteries prepared in Comparative Example 1 and Example 6;
[0027] Figure 7 The aqueous zinc ion full battery prepared in Comparative Example 1 and Example 1 was -1 Cyclic performance curve below;
[0028] Figure 8 Schematic diagram of the mechanism by which the additive molecules in the present invention modify the aqueous electrolyte to improve the stability of the zinc negative electrode. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the preferred embodiments of the present invention are further described in detail in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] An aqueous zinc ion battery electrolyte, the preparation method of which is as follows:
[0032] 2 mmol of ZnSO4 and 0.05 mmol of O-phosphoethanolamine powder were dissolved in 100 mL of deionized water, magnetically stirred at room temperature for 30 min at a stirring rate of 400 r / min, and then ultrasonically treated for 20 min at an ultrasonic power of 200 W to obtain an aqueous zinc ion battery electrolyte.
[0033] Example 2
[0034] An aqueous zinc ion battery electrolyte, the preparation method of which is as follows:
[0035] 2 mmol of ZnSO4 and 2 mmol of O-phosphoethanolamine powder were dissolved in 100 mL of deionized water, magnetically stirred at room temperature for 30 min at a stirring rate of 400 r / min, and then ultrasonically treated for 20 min at an ultrasonic power of 200 W to obtain an aqueous zinc ion battery electrolyte.
[0036] Example 3
[0037] An aqueous zinc ion battery electrolyte, the preparation method of which is as follows:
[0038] 1 mmol of ZnSO4 and 2 mmol of O-phosphoethanolamine powder were dissolved in 100 mL of deionized water, magnetically stirred at room temperature for 30 min at a stirring rate of 400 r / min, and then ultrasonically treated for 20 min at an ultrasonic power of 200 W to obtain an aqueous zinc ion battery electrolyte.
[0039] Example 4
[0040] An aqueous zinc ion battery electrolyte, the preparation method of which is as follows:
[0041] 0.5 mmol of ZnSO4 and 0.5 mmol of O-phosphoethanolamine powder were dissolved in 100 mL of deionized water, magnetically stirred at room temperature for 30 min at a stirring rate of 400 r / min, and then ultrasonically treated for 20 min at an ultrasonic power of 200 W to obtain an aqueous zinc ion battery electrolyte.
[0042] Example 5
[0043] An aqueous zinc ion battery electrolyte, the preparation method of which is as follows:
[0044] 2 mmol of ZnSO4 and 2 mmol of O-phosphoethanolamine powder were dissolved in 100 mL of deionized water, magnetically stirred at room temperature for 5 min at a stirring rate of 100 r / min, and then ultrasonically treated for 20 min at an ultrasonic power of 200 W to obtain an aqueous zinc ion battery electrolyte.
[0045] Example 6
[0046] 2 mmol of ZnSO4 and 2 mmol of O-phosphoethanolamine powder were dissolved in 100 mL of deionized water, magnetically stirred at room temperature for 30 min at a stirring rate of 400 r / min, and then ultrasonically treated for 5 min at an ultrasonic power of 100 W to obtain an aqueous zinc ion battery electrolyte.
[0047] Comparative Example 1
[0048] An aqueous zinc ion battery electrolyte, the preparation method of which is as follows:
[0049] 2 mmol of ZnSO4 was dissolved in 100 mL of deionized water, and magnetically stirred at room temperature for 30 min at a stirring rate of 400 r / min, followed by ultrasonication for 20 min at an ultrasonic power of 200 W to obtain a 2 mol / L ZnSO4 electrolyte.
[0050] Aqueous zinc ion Zn / / Cu batteries and aqueous zinc ion full batteries were prepared using the electrolytes described in Examples 1 to 6 and Comparative Example 1, wherein the preparation method of the aqueous zinc ion full battery is as follows:
[0051] The preparation method of the Zn / / Cu battery is to assemble a zinc foil with a diameter of 16 mm and a thickness of 0.1 mm and a glass fiber separator containing electrolyte with a diameter of 16 mm in the order of zinc foil-separator (electrolyte)-zinc foil into a Zn / / Zn battery; and to assemble a zinc foil with a diameter of 16 mm and a thickness of 0.1 mm as a negative electrode and a copper foil with a diameter of 16 mm and a thickness of 0.1 mm as a positive electrode into a Zn / / Cu battery in the order of zinc foil-separator (electrolyte)-copper foil. The amount of electrolyte added is 80 μL.
[0052] The preparation method of the aqueous zinc ion full battery is as follows: first, 0.585g of NH4VO3 is added to 35mL of deionized water. 0.946g of oxalic acid powder is added to the solution and stirred magnetically. The solution is transferred to a 50mL hydrothermal kettle and heated at 140°C for 12h. After cooling, the product is collected, washed with deionized water, and then dried at 70°C overnight to finally obtain NH4V4O 10Powder. The product was uniformly stirred with a conductive agent and a binder at a mass ratio of 7:2:1 at 500r / min for 24h, and then coated on a stainless steel foil, and then dried in an oven at 80°C for 12h to obtain a positive electrode sheet for an aqueous zinc ion battery. The conductive agent is SuperP, and the binder is polyvinylidene fluoride;
[0053] Then, the positive electrode sheet is stacked together with the glass fiber separator containing electrolyte and commercial zinc foil in sequence, packaged using a battery packaging machine, and assembled into an aqueous zinc ion full battery.
[0054] The aqueous zinc ion symmetric batteries obtained in Comparative Example 1 and Example 1 were heated to 1 mA cm -2 The current density is 1 mAh cm -2 The cyclic test was carried out at a deposition density of Figure 1 As shown, it can be seen that the aqueous zinc ion symmetric battery containing O-phosphoethanolamine additive has better cycling stability.
[0055] The aqueous zinc ion symmetric batteries obtained in Comparative Example 1 and Example 4 were heated at 5 mA cm -2 The current density is 5 mAh cm -2 The cyclic test was carried out at a deposition density of Figure 2 As shown, it can be seen that the aqueous zinc ion symmetric battery containing O-phosphoethanolamine additive has better cycling stability.
[0056] The aqueous zinc ion symmetric batteries obtained in Comparative Example 1 and Example 5 were cycled at different current densities. The results are as follows: Figure 3 As shown, it can be seen that the aqueous zinc ion symmetric battery containing O-phosphoethanolamine additive has better rate performance.
[0057] The aqueous zinc ion Zn / / Cu batteries obtained in Comparative Example 1 and Example 3 were heated to 1 mA cm -2 The current density is 0.5 mAh cm -2 The cyclic test was carried out at a deposition density of Figure 4 As shown, it can be seen that the coulombic efficiency stability of aqueous zinc ion batteries containing O-phosphoethanolamine additive is better.
[0058] The aqueous zinc ion Zn / / Cu batteries obtained in Comparative Example 1 and Example 2 were heated at 5 mA cm -2 Current density, 1 mAh cm -2 The cyclic test was carried out at a deposition density of Figure 5 As shown, it can be seen that the coulombic efficiency stability of aqueous zinc ion batteries containing O-phosphoethanolamine additive is better.
[0059] The electrodes of the aqueous zinc ion Zn / / Cu battery obtained in Comparative Example 1 and Example 6 after cycling were subjected to X-ray diffraction test. The results are as follows: Figure 6 As shown, it can be seen that the intensity of the characteristic peak of the byproduct on the surface of the negative electrode of the aqueous zinc ion battery containing O-phosphoethanolamine additive is smaller.
[0060] The aqueous zinc ion batteries obtained in Comparative Example 1 and Example 1 were heated to 1Ag -1 The cycle test was carried out at a current density of Figure 7 As shown, it can be seen that the aqueous zinc-ion battery containing O-phosphoethanolamine additive performs better.
[0061] Figure 8 The mechanism of action of O-phosphoethanolamine additive on the zinc anode interface and electrolyte coordination environment is demonstrated.
[0062] Compared with existing electrolyte additives, the aqueous zinc ion battery electrolyte additive proposed by the present invention has the advantages of high biocompatibility, low cost and excellent electrochemical performance, which is conducive to promoting the practical application of aqueous zinc ion batteries.
[0063] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. An aqueous zinc ion battery electrolyte, characterized in that Includes zinc salt, O-phosphoethanolamine and water.
2. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that The concentration of O-phosphoethanolamine in the electrolyte is 0.01-2 mol / L.
3. The aqueous zinc ion battery electrolyte according to claim 2, characterized in that The concentration of O-phosphoethanolamine in the electrolyte is 0.1-1 mol / L.
4. The aqueous zinc ion battery electrolyte according to claim 1, characterized in that The zinc salt includes any one or more of zinc sulfate, zinc chloride, zinc nitrate and zinc trifluoromethanesulfonate.
5. The aqueous zinc ion battery electrolyte according to claim 4, characterized in that The concentration of the zinc salt in the electrolyte is 0.1-3 mol / L.
6. The aqueous zinc ion battery electrolyte according to claim 5, characterized in that The concentration of zinc salt in the electrolyte is 1-2 mol / L.
7. The method for preparing an aqueous zinc ion battery electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: Zinc salt and O-phosphoethanolamine are added into water, and mechanical stirring and ultrasonic treatment are carried out successively at room temperature to obtain an aqueous zinc ion battery electrolyte.
8. The preparation method according to claim 7, characterized in that: The mechanical stirring speed is 100 r / min to 600 r / min, and the mechanical stirring time is 5 min to 60 min.
9. The preparation method according to claim 7, characterized in that: The ultrasonic power of the ultrasonic treatment is 50W to 600W, and the ultrasonic time is 5min to 60min.
10. The use of the aqueous zinc ion battery electrolyte according to any one of claims 1 to 6, characterized in that: The aqueous zinc ion battery is prepared by using the aqueous zinc ion battery electrolyte.
